Enabling technologies for next generation wireless communications - Usman, Mohammed (Electrical engineering professor); Wajid, Mohd; Ansari, Mohd Dilshad (Boca Raton, FL : CRC Press/Taylor & Francis Group, LLC, 2021)
"This book provides up-to-date information on emerging trends in wireless systems, their enabling technologies and their evolving application paradigms. This book includes the latest trends and developments towards next generation wireless communications. It highlights the requirements of next generation wireless systems, limitations of existing technologies in delivering those requirements and the need to develop radical new technologies. It focuses on bringing together information on various technological developments that are enablers for fulfilling the requirement of future wireless communication systems and their applications. Topics include spectrum issues, network planning, signal processing, transmitter, receiver, antenna technologies, channel coding, security and application of machine learning and deep learning for wireless communication systems. The book also provides information on enabling business models for future wireless systems. Useful as a resource for researchers and practitioners world-wide, including industry practitioners, technologists, policy decision-makers, academicians, and graduate students"--
OCLC-licensed vendor bibliographic record.
Keywords: Wireless communication systems -- Technological innovations